Evaluación de la eficiencia de conducción del canal principal del Sistema de Riego El Ingenio (SRI), del Cantón Espíndola, Provincia de Loja - Torres Jiménez, Esvin Paul (2024)
The main canal of the El Ingenio Irrigation System, built in 1986, presents technical and maintenance problems that affect its efficiency. Obstructions were identified in the intake works and a high degree of deterioration in the buffer mattress, cracks and settlements in the canal, causing water losses and reducing the system's distribution capacity to the irrigation area. The gauging carried out with the micro windlass shows that the E section has higher volumetric losses (0.29 l s-1 km-1), compared to the N section (0.11 l s-1 km-1), which correlates with its state of conservation. In comparison with other studies. The lack of preventive and corrective maintenance has contributed to this deterioration, in line with FAO recommendations on the importance of maintenance to extend the useful life of the infrastructure. It was determined that sections B and N have an efficiency of 100%, while sections E and I have a critical efficiency of 55%. The average efficiency of the canal is 88.17%, considered good according to Villavicencio's classification. However, the efficiency in critical sections indicates the urgent need to implement rehabilitation measures.